Gut microbiota facilitates adaptation of the plateau zokor (Myospalax baileyi) to the plateau living environment - Hu, Bin; Wang, Jiamin; Li, Ying; Ge, Jin; Pan, Jinchao; Li, Gaojian; He, Yongcai; Zhong, Haishun; Wang, Bo; Huang, Yanyi; Han, Shuyi; Xing, Yanan; et al. (Frontiers in Microbiology, 2023)
Gut microbiota not only helps the hosts to perform many key physiological functions such as food digestion, energy harvesting and immune regulation, but also influences host ecology and promotes host adaptation to extreme environments. Plateau zokors epitomize successful physiological adaptation to their environment in the face of the harsh environment characterized by low temperature, low pressure and hypoxia in the Tibetan plateau region and high concentrations of CO2 in their burrows. Therefore, here we used a metagenomic sequencing approach to explore how gut microbiota contributed to the adaptive evolution of the plateau zokor on the Qinghai-Tibet Plateau. Our metagenomic results show that the gut microbiota of plateau zokors on the Tibetan plateau is not only enriched in a large number of species related to energy metabolism and production of short-chain fatty acids (SCFAs), but also significantly enriched the KO terms that involve carbohydrate uptake pathways, which well address energy uptake in plateau zokors while also reducing inflammatory responses due to low pressure, hypoxia and high CO2 concentrations. There was also a significant enrichment of tripeptidyl-peptidase II (TPPII) associated with antigen processing, apoptosis, DNA damage repair and cell division, which may facilitate the immune response and tissue damage repair in plateau zokors under extreme conditions. These results suggest that these gut microbiota and their metabolites together contribute to the physiological adaptation of plateau zokors, providing new insights into the contribution of the microbiome to the evolution of mammalian adaptation.